O47: IKK-ALPHA AS A POTENTIAL NOVEL TARGET FOR TREATMENT OF COLORECTAL CANCER. (27th April 2021) - Patel, M; Quinn, JA; Pennel, KAF; Flanagan, D; Horgan, PG; McMillan, DC; MacKay, S; Sansom, O; Edwards, J
Abstract: Introduction: There is substantial evidence linking NF-κB and cancer-related processes. The aim of this study was to investigate the role of IKKα, the main catalytic component of non-canonical NF-κB pathway in colorectal cancer (CRC). Method: Immunohistochemistry and immunofluorescence was used to examine expression of IKKα in 1030 patients undergoing resection for stage I-III CRC. To assess IKKα inhibition, organoids were prepared from wild type (WT) mouse colon, mouse models of CRC (Apc and Apc.KRAS.pT53.TGFbR2 (AKPT)) and patient derived human organoids. These were treated with an IKKα inhibitor, SU1433 and organoid size and cell viability assessed. Result: High cytoplasmic expression of IKKα was associated with increasing T stage (p=0.012), poor tumour differentiation (p=0.010), tumour necrosis (p=0.013) and low proliferation status (p=0.013). High punctate IKKα expression was associated with reduced CSS (HR1.20 95%CI 1.02-1.42, p<0.001). Immunofluorescence showed IKKα was co-located with a Golgi-related structure. SU1433 did not significantly impact on WT (C57/B16) organoid viability up to a concentration of 1uM, however organoid size and cell viability was significantly reduced in a dose-dependent manner in organoids from both Apc and AKPT mouse models. A similar reduction was observed in patient derived human organoids. Conclusion: Punctate IKKα expression was associated with poor cancer specific survival in CRC patients. The relationship between IKKα and the Golgi requires further investigation. Inhibition with SU1433, impacted on CRC mouse and patient derived human organoid size and cell viability. These results suggest that IKKα following further investigation could be employed as a novel therapeutic target in CRC. Take-home message: IKKα is up-regulated in patients undergoing surgery for CRC, this is associated with poor survival outcome and inhibition of IKKα and has presented itself as a novel therapeutic target. The relationship between IKKα and the Golgi has raised interesting questions regarding the molecular behaviour of IKKα and this warrants further investigation.